A case of reverse takotsubo cardiomyopathy caused by an eating disorder. Issue 3 (March 2017) - Tagami, Travis; Mertens, Amy; Rothschild, Daniel; Chowdhury, Pertha
Abstract: Takotsubo cardiomyopathy is an acquired transient cardiomyopathy that causes severe systolic dysfunction in the absence of coronary disease. Here we present a case of reverse takotsubo cardiomyopathy. A 67-year-old female was admitted for weakness and falls due to severe malnutrition. During her stay she was diagnosed with an eating disorder. She also developed chest pain during her hospitalization and was taken urgently for catheterization which showed normal coronary arteries with akinetic basal and inferior walls and hyperkinesis of the apex. Her ejection fraction decreased to 25% from 60% five days previously. She was diagnosed with reverse takotsubo. She was placed on an appropriate heart failure regimen and eventually transferred to inpatient rehabilitation. In its typical form, takotsubo causes apical ballooning due to hyperkinetic basal and inferior wall motion and apical hypokinesis. Reverse takotsubo causes a depressed basal segment with apical hyperkinesis usually brought on by severe emotional or physical stress. Our case is the first documented report of an eating disorder causing the reverse type of takotsubo cardiomyopathy. <Learning objective: The reader will be able to recognize stress-induced cardiomyopathy in the right clinical setting and understand that there are different variants of this condition that can present with multiple different wall motion abnormalities.>